Spirituality and subjective well-being among Ghanaian older adults: optimism and meaning in life as mediators. (1st February 2021) - Aglozo, Eric Yao; Akotia, Charity Sylvia; Osei-Tutu, Annabella; Annor, Francis
Abstract: Objective: This cross-sectional study investigated the relationship between spirituality and subjective well-being (positive affect, negative affect, and life satisfaction), and whether this relationship is mediated by optimism and meaning in life. Method: Participants were 235 older adults (≥60 years) conveniently sampled from Ghanaian communities. Structural equation modeling (SEM) was used to test the direct and indirect relationships. Sobel test was also used to test specific mediating effects of optimism and meaning in life. Results: Spirituality was positively related with positive affect and life satisfaction, but negatively related with negative affect. The SEM results revealed that the relationship between spirituality and subjective well-being was indirect. Sobel test showed that the mediating effect of optimism was only statistically significant for negative affect but not positive affect and life satisfaction. In contrast, the mediating effect of meaning in life was statistically significant for the three components of subjective well-being. Conclusion: The study has demonstrated that spirituality indirectly influences subjective well-being through optimism and meaning in life. It also showed the relative importance of meaning in life over optimism as a mediator. Theoretical and practical implications of these findings have been discussed.